Tindak Tutur Ilokusi Tokoh Utama dalam Novel Rasa Karya Tere Liye - Bangkit Adi Swasono (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Humans as social beings, canot live alone and are always connected with other people. In communication, humans do not merely speak but also perform actions known as speech acts. There are three types of speech acts, namely locutionary, illocutionary, and perlocutionary. In relationto this, the researcher formulated a research problem how are the directive, commissive, and expressivve illocutionary acts of the main character in the novel Rasa by Tere Liye?. The aim of this research is to obtain an objective description of the directive, commissive, and expressive illocutionary acts of the main character in the novel Rasa by Tere Liye. This research uses a qualitative descriptive method. The data sources is in the speech of the main character of the novel Rasa by Tere Liye. Data collection techniques include reading techniques and note taking techniques. The results of the research found fifty data on directive illocutionar speech acts, thirty data on commissive illocutionary speech acts, and twenty eight data on expressive illocutionary speech acts.